2011
DOI: 10.1007/s10681-011-0566-z
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters and gains for color traits of strawberry

Abstract: An investigation of strawberry (Fragaria 9 ananassa Duch.) fruit and juice color dimensions (L* a* b*) was conducted to estimate genetic parameters and determine breeding strategies for improving fruit color in the University of Florida strawberry breeding population. The genetic analysis was conducted using clonally replicated seedlings from a factorial mating design with additional biparental crosses and was evaluated in two locations. Substantial additive and non-additive genetic variation was described for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
9
0
2
Order By: Relevance
“…When low interaction effects were considered, MAC, DPPH, and TEAC were rather stable and might be useful as selection criteria for improvement of corn genotypes with high antioxidant capacity. The low interactions of genotype 9 environment are preferable, indicating that the relative performance in one season is reliable in predicting relative performance in another season (Knievel et al 2009;Hasting et al 2012;Mahan et al 2013). With low G 9 E interaction and little error variance, the relative performance across seasons or environment should be similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When low interaction effects were considered, MAC, DPPH, and TEAC were rather stable and might be useful as selection criteria for improvement of corn genotypes with high antioxidant capacity. The low interactions of genotype 9 environment are preferable, indicating that the relative performance in one season is reliable in predicting relative performance in another season (Knievel et al 2009;Hasting et al 2012;Mahan et al 2013). With low G 9 E interaction and little error variance, the relative performance across seasons or environment should be similar.…”
Section: Discussionmentioning
confidence: 99%
“…Kernel color can be easily identified visually and, therefore, can be increased through phenotypic selection (Rodriguez et al 2013;Shen et al 2009). Although visual assessment is and an easy method, it lacks consistency due to human is poor in color memory and compromises genotype comparisons (Hasting et al 2012;Hutchings 1999). The application of colorimetric systems, based on uniform color spaces (CIELUV and CIELAB) and non-uniform color spaces (CIE-XYZ), is of great value for the quantification and characterization of the color properties of diverse pigments and foods (Hernanz et al 2008;Wrolstad et al 2005;Yang et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Isso exige que melhoristas de morangueiro selecionem genótipos também com base em atributos de cor, lançando cultivares altamente atraentes para os consumidores. Tradicionalmente, os melhoristas têm como objetivo, desenvolver morangos com coloração externa e interna vermelho-brilhante (Hasing et al, 2012).…”
Section: Genótipos Escala De Notasunclassified
“…By comparison, Shaw (1991) and Hasing et al (2012) demonstrated in their studies that phenotypic and genetic correlations between skin colour and flesh colour of strawberry fruit (as measured by chromatography) were low or moderate, but below the level of significance. For the other pairs of traits, the correlation coefficient was less than 0.5, and for a large majority of them was below the level of significance.…”
Section: Resultsmentioning
confidence: 99%